2014
DOI: 10.1103/physreve.89.062404
|View full text |Cite
|
Sign up to set email alerts
|

Reorientation of a dipolar monolayer and dipolar solvent

Abstract: The reliable persistence of an adhered monolayer film on a substrate is critical for film function. The process by which monolayers degrade or disperse remains unclear. Our study investigates the properties and dynamics of a solute of dipolar molecules initially adhered as a monolayer on a substrate in a water-like Stockmayer solvent. We find that for a rigid solute, both the solute and solvent show qualitatively different dynamics than for a flexible solute and its solvent. For the rigid solute, spreading is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…32 Theoretically, Yi and Gao 33 and Ding and Ma 30 have found that soft particles can hardly achieve full wrapping. Besides a recent theoretical work also showed that rod-shaped elastic nanoparticles can exhibit a similar elasticity-dependent effect on cell uptake, 34 and consistently, our previous simulation results indicated that the endocytosis of a soft vesicle becomes rather difficult. 35 Based on the above studies, we put forward here the idea that for drug delivery, NP hardness can be used to control the pathways for NP uptake, and emphasize the importance of nanocarrier hardness on achieving high drug efficacy.…”
Section: Introductionsupporting
confidence: 79%
“…32 Theoretically, Yi and Gao 33 and Ding and Ma 30 have found that soft particles can hardly achieve full wrapping. Besides a recent theoretical work also showed that rod-shaped elastic nanoparticles can exhibit a similar elasticity-dependent effect on cell uptake, 34 and consistently, our previous simulation results indicated that the endocytosis of a soft vesicle becomes rather difficult. 35 Based on the above studies, we put forward here the idea that for drug delivery, NP hardness can be used to control the pathways for NP uptake, and emphasize the importance of nanocarrier hardness on achieving high drug efficacy.…”
Section: Introductionsupporting
confidence: 79%
“…3,4 Therefore, there is an urgent need for a better understanding of the interaction between NPs and cell membranes. 5 At present, a large number of experimental and theoretical studies have demonstrated that the size, [6][7][8][9][10] shape, [11][12][13][14][15][16][17][18][19][20] orientation, [21][22][23][24][25][26] stiffness, [27][28][29][30][31] and surface properties [32][33][34][35] of NPs will affect the cellular uptake of NPs. Recent experimental studies have shown that when the radius of the NPs is less than 15 nm, a group of NPs can be internalized by cells or polymersomes as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…Intuitively, elastic particles are less able to undergo complete wrapping than comparable rigid particles. The binding of rigid particles to the cell membrane allows only the membrane to deform, whereas for elastic particles both the membrane and the particle deform [97][98][99][100] . This approach has also been applied to the problem of exocytosis of elastic particles 101 .…”
Section: Elastic Nano-engineered Particlesmentioning
confidence: 99%
“…of inhibited wrapping for elastic particles is also observed for a similar model that contains stochastic receptor-ligand binding, rather than instantaneous deterministic binding 100 . Elastic particles can undergo asymmetric wrapping, in contrast to stiff particles which undergo reorientation in the same parameter regimes 99 . Rotation during the internalisation process appears in both molecular and particle dynamics simulations 43 , and allows for the maximisation of the contact area between the particle and the cell membrane.…”
Section: Elastic Nano-engineered Particlesmentioning
confidence: 99%